PEMULIHAN STOK TANGKAPAN PERIKANAN TERIPANG DI KEPULAUAN SERIBU: SUATU PENDEKATAN EKOSISTEM - Am Azbas Taurusman; Dadang Shafrudin; Tri Wiji Nurani; Didin Komarudin (Bogor Agricultural University, 2018)
ABSTRACT Kepulauan Seribu known as Thousand Islands is one of the sea cucumbers producing centers in Indonesia. Sea cucumber has been considered as one of the fishery export commodities with high selling prices. In the last two decades, the catch has been indicating a serious declining. The high intensity of catching and habitat degradation are two main factors that threaten the sustainability of sea cucumber fisheries. In order to recovery the stock, a restocking program in frame of ecosystem approach to fishery has been piloted in Thousand Islands, Jakarta. This research covers the bio-technical aspects of sea cucumber fisheries in an integrated manner with the ecosystem approach. There were several steps in conducting the restocking study, namely the study of habitat status and feasibility, preparation of maintenance sites for biota, seed spreading, monitoring and evaluation. A well coordination and collaboration with local institutions (Kepulauan Seribu National Park) was needed to build previously. The results of the study indicated that efforts to restore sea cucumber fisheries should be integrated with conservation of seagrass ecosystems which as sea cucumbers habitat and a proper maintenance system. Eight species of sea cucumbers, consist of 4 species of Holothuridae (Bohadschia bivittata, Actinopyga lecanora, Holothuria leucospilota, H. scabra), and 4 species Stichopodidae (Stichopus herrmanni, S. ocellatus, S. horren, S. monotuberculatus) have been identified and restocking in this area. The released biota can live and grow well and breed at the research site. The construction of seagrass-based sea cucumber ecosystem restocking system has become one of the new tourist attractions integrated with the Thousand Islands National Park tourist facilities, which are very attractive to visitors. Keywords: ecosystem approach fishery managemen (EAFM), restocking, sea cucumbers fishery, seagrass ecosystem ABSTRAK Kepulauan Seribu merupakan salah satu sentra penghasil teripang di Indonesia. Teripang merupakan salah satu komoditi ekspor perikanan dengan harga jual yang tinggi. Dalam dua dekade terakhir, tangkapan teripang telah menunjukkan penurunan tajam. Tingginya intensitas penangkapan dan degradasi habitat merupakan dua faktor utama yang mengancam keberlanjutan perikanan teripang. Salah satu upaya untuk pemulihan stok teripang melalui pendekatan ekosistem telah diujicobakan di wilayah Kepulauan Seribu, Jakarta. Tulisan ini mencakup aspek bio-teknis upaya pemulihan perikanan teripang secara terintegrasi dengan pendekatan ekosistem. Upaya pemulihan dilakukan melalui beberapa tahap, yaitu studi status dan kelayakan habitat, penyiapan wadah pemeliharaan biota, penebaran benih, monitoring dan evaluasi. Sebelum kegiatan dilakukan, terlebih dahulu melakukan koordinasi dengan institusi lokal (Balai Taman Nasional Kepulauan Seribu). Hasil kajian menunjukkan bahwa upaya pemulihan perikanan teripang harus diselaraskan dengan upaya konservasi ekosistem lamun sebagai habitat teripang dan sistem pemeliharaan yang layak secara teknis. Delapan spesies teripang, terdiri dari 4 spesies Holothuridae (Bohadschia bivittata, Actinopyga lecanora, Holothuria leucospilota, H. scabra), dan 4 species Stichopodidae (Stichopus herrmanni, S. ocellatus, S. horren, S. monotuberculatus) telah terindentifikasi dan di-restocking di lokasi ini. Biota yang dilepas dapat hidup dan tumbuh dengan baik dan berkembangbiak di lokasi penelitian. Konstruksi sistem restocking teripang berbasis ekosistem lamun telah menjadi salah satu obyek wisata baru terintegrasi dengan fasilitas wisata Taman Nasional Kepulauan Seribu, yang sangat menarik bagi pengunjung. Kata kunci: pendekatan ekosistem (EAFM), restocking, perikanan teripang, ekosistem lamun